Pengaruh Service Performance dan Fasilitas Baggage Conveyor Belt terhadap Kepuasan Penumpang Maskapai Lion Air Dalam Pengambilan Bagasi di Bandar Udara Mopah Merauke - Fatimah, Aisyah Nur; Fatmayati, Fryda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Mopah Airport Merauke is an airport located in the city of Merauke, South Papua, Indonesia. The purpose of this study was to determine whether the effect of service performance and baggage conveyor belt facilities on Lion Air airline passenger satisfaction in baggage claim at Mopah Airport Merauke. This research uses quantitative research methods. This research was conducted at Mopah Airport Merauke where the objects of this research were passengers or the people in the city of Merauke. The source of the data used in this study was obtained from distributing questionnaires to respondents of Lion Air airline passengers at Mopah Airport Merauke. The number of samples in this study is 100 respondents determined by the slovin formula. The results of this study were concluded to answer the formulation of the problem, that: 1. The Influence Variable of Service Performance (X1) has an effect on the Passenger Satisfaction Variable (Y) as evidenced by the calculated T value on the variable effect of service performance (X1) which is greater than T table, namely 8,636 > 1,660 with a Sig value. smaller than the probability value of 0.000 <0.05; 2. The Baggage Conveyor Belt Facility Variable (X2) has an effect on the Passenger Satisfaction Variable (Y) as evidenced by the calculated T value being greater than T table, namely 11,118 > 1,660 with a Sig. smaller than the probability value of 0.000 <0.05; 3. The effect of service performance (X1), the baggage conveyor belt facility (X2) has an effect on the passenger satisfaction variable (Y) of 0.604, it is known from the R Square value, which means that the variables X1, X2 affect the Y variable by 60.4%. Keywords: effect of service performance, bcb facilities, mopah airport merauke.